2014
DOI: 10.1007/s12011-014-0057-x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Heavy Metals and Trace Elements in Umbilical Cord Blood and the Risk of Adverse Pregnancy Outcomes: a Population-Based Study

Abstract: To better understand the relationship between prenatal exposure to heavy metals and trace elements and the risk of adverse pregnancy outcomes, we investigated the status of heavy metals and trace elements level in a Chinese population by collecting umbilical cord blood. Umbilical cord blood heavy metals and trace elements concentrations were determined by inductively coupled plasma-mass spectrometry. No differences with statistical significance in the median arsenic (As), cadmium (Cd), cobalt (Co), chromium (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 30 publications
3
40
1
3
Order By: Relevance
“…In the same way, metalinduced oxidative stress seems to play an important role in the etiology of other chronic diseases, such as cardiovascular and respiratory diseases, neurological disorders, etc (Jomova and Valko, 2011). Furthermore, accumulating evidence provides correlations between the exposure to trace elements and various adverse effects, such as those recently found for Ti, Cu, Cd, Rb and altered heart rate variability (Feng et al, 2015), for Cs and Sb and high blood pressure (Shiue and Hristova, 2014), for Ti and Sb and the risk of adverse pregnancy outcomes (Zheng et al, 2014), and for Cd and Mn and cognition and behavior in childhood (Sanders et al, 2015). Additional evidences of detrimental effects for human health, albeit more limited and recovered in occupational scenarios or in very polluted areas, were found also for Ga (Chen, 2007), Li, B, and Sr (Usuda et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way, metalinduced oxidative stress seems to play an important role in the etiology of other chronic diseases, such as cardiovascular and respiratory diseases, neurological disorders, etc (Jomova and Valko, 2011). Furthermore, accumulating evidence provides correlations between the exposure to trace elements and various adverse effects, such as those recently found for Ti, Cu, Cd, Rb and altered heart rate variability (Feng et al, 2015), for Cs and Sb and high blood pressure (Shiue and Hristova, 2014), for Ti and Sb and the risk of adverse pregnancy outcomes (Zheng et al, 2014), and for Cd and Mn and cognition and behavior in childhood (Sanders et al, 2015). Additional evidences of detrimental effects for human health, albeit more limited and recovered in occupational scenarios or in very polluted areas, were found also for Ga (Chen, 2007), Li, B, and Sr (Usuda et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results show higher urinary levels of most of the studied compounds in children exposed to ETS compared to unexposed, with the exception of V and Pb. Several adverse effects for human health have been related to the exposure to all of the monitored trace elements (Chen, 2007;Feng et al, 2015;Jomova and Valko, 2011;Lee et al, 2012;Sanders et al, 2015;Shiue and Hristova, 2014;Usuda et al, 2007;Zheng et al, 2014). Scientific evidence of these effects has grown considerably over the years, and more and new findings continue to emerge from the researches in this field.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies did not find any relationship between Cd levels in maternal or cord blood and size at birth. 7178 There are currently no epidemiologic studies that have evaluated the association between Cd exposure during the early pregnancy period and fetal development and birth outcomes.…”
Section: Effects Of Environmental Exposures On Fetal and Childhoodmentioning
confidence: 99%
“…Recent studies of arsenic (As) and pregnancy outcomes did not find an association between prenatal As exposure and adverse pregnancy outcomes, 78,95 while three studies conducted in Bangladesh where higher levels of As were found in the drinking water reported an increased risk of adverse birth outcomes (Table 2). 9698 One of the studies found that the influence of As on fetal growth appeared to be sex-dependent with an inverse association with fetal size in boys.…”
Section: Effects Of Environmental Exposures On Fetal and Childhoodmentioning
confidence: 99%
“…Cd pollution has become a major health concern in China owing to the industrial emissions and the mass consumption of plant-derived food such as rice which contained high levels of Cd transferred from soil (Du et al, 2013;Uraguchi and Fujiwara, 2012). However, few data are available on the effects of prenatal exposure to Cd on birth outcomes in Chinese populations (Hu et al, 2015;Lin et al, 2011;Sun et al, 2014;Zheng et al, 2014). Given this background, we took advantage of our large prospective mother-child cohort to assess the effects of maternal Cd exposure on birth outcomes in 5364 Chinese pregnant women.…”
Section: Introductionmentioning
confidence: 99%